Efficiency Of Steam Production Analysis At Pulp And Paper Industry - Marlina '; Evi Sribudiani; Sudarmalik ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Companies must be able to regulate the allocation of factors of production to increase productivity and improve production. The aim of this research are : 1) to know calculation of steam production cost, 2) to know the most factors that influence the production of steam, 3) to know efficiency of steam production cost. Research location is at PT. Indah Kiat Pulp and Paper. The sample was taken from steam production cost on Januari 2010 until December 2010. Data was analyzed with doubled-linier regression analysis with Cobb-Douglas production function, analysis of the costs, analysis of factors affecting the production of steam production and analysis of efficiency. The result showed that 1) total cost of steam production per month is Rp2.864.159.747,64, 2) from the doubled-linier regression analysis is known only bark variable that significantly affected to the production of steam, 3) from the analysis of efficiency is obtained that the use of bark,diesel oil, and heavy oil is efficient for steam production, it was 283,3%. Keywords : steam production, efficiency, production factors